Self‐Assembly of Hierarchical Chiral Nanostructures Based on Metal–Benzimidazole Interactions: Chiral Nanofibers, Nanotubes, and Microtubular Flowers. Issue 34 (1st June 2016) - Zhou, Xiaoqin; Jin, Qingxian; Zhang, Li; Shen, Zhaocun; Jiang, Long; Liu, Minghua
Abstract : Controlled hierarchical self‐assembly of synthetic molecules into chiral nanoarchitectures to mimic those biological chiral structures is of great importance. Here, a low‐molecular‐weight organogelator containing a benzimidazole moiety conjugated with an amphiphilicl ‐glutamic amide has been designed and its self‐assembly into various hierarchical chiral nanostructures is investigated. Upon gel formation in organic solvents, 1D chiral nanostructure such as nanofiber and nanotube are obtained depending on the solvents. In the presence of transition and rare earth metal ions, hierarchical chiral nanostructures are formed. Specifically, the addition of TbCl3, EuCl3, and AgNO3 leads to nanofiber structures, while the addition of Cu(NO3 )2, Tb(NO3 )3, or Eu(NO3 )3 provides the microflower structures and microtubular flower structures, respectively. While Eu(III) and Tb(III)‐containing microtubular flowers keep the chirality, the Cu(II)‐coordinated microflowers lose chirality. More interestingly, the nanofibers formed by the gelator coordinated with Eu(III) or Tb(III) ions show not only the supramolecular chirality but also the circularly polarized luminescence. Abstract : Hierarchical chiral nanostructures including chiral fibers, nanotubes, and microtubular flower‐like structures are obtained by the self‐assembly of benzimidazole amphiphile and metal ions.